2017
DOI: 10.1002/ccr3.1295
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgery of aortic thrombosis in a dog using Fogarty maneuver – technical feasibility

Abstract: Key Clinical MessageAortic thromboembolism is a rare and life‐threatening disease in dogs. This report aims to describe the successful surgical treatment by use of a Fogarty Thrombectomy Catheter in an 8‐year‐old patient. The postsurgical intensive care therapy to prevent ischemia‐reperfusion syndrome is specified, despite poor outcome in our case (owner elected euthanasia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…In a case report, on the first postoperative day, the patient had pelvic limb edema and acidosis, indicating a ischemia-reperfusion syndrome [21]. In our case, the animal did not have clinical signs compatible with reperfusion syndrome in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…In a case report, on the first postoperative day, the patient had pelvic limb edema and acidosis, indicating a ischemia-reperfusion syndrome [21]. In our case, the animal did not have clinical signs compatible with reperfusion syndrome in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 44%
“…Schwede et al [21] conducted a study where tomography confirmed the previous diagnosis of ultrasound. The diagnosis of thrombi can be made by ultrasonography examination of the abdomen, computed tomography, and nuclear magnetic resonance [17].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hay varios factores que determinan la aparición o formación de trombos y se agrupan en la triada de Virchow, la cual está representada por: Éstasis sanguínea, lesión endotelial, y estado de hipercoagulabilidad (cambio en el equilibrio sistémico de factores procoagulantes y anticoagulantes), en base a la triada se establece el diagnóstico de trombosis, especialmente en gatos [25].…”
Section: Introductionunclassified